Analysis of industrial enterprises innovative activity in Ukraine and in Lviv region, in particular - Tsohla, О. O. (Видавництво Львівської політехніки, 2014)
The analysis of the innovative activity of industrial enterprises in Ukraine and, particularly, in Lviv region in 2011–2012 is presented in the article. The investment activity in the domestic economy according to the International ratings is analyzed. The innovation potential of the Ukrainian industry is estimated. The factors affecting the state of innovative activities that has recently shaped in the Ukrainian economy are determined. Проаналізовано інноваційну активність промислових підприємств України, зокрема Львівської області, за 2011–2012 рр. Досліджено інноваційну активність вітчизняної економіки згідно з міжнародними рейтингами. Здійснено оцінку інноваційного потенціалу промисловості України. Визначено фактори, які впливають на інноваційне становище, що склалося останніми роками в економіці України.
Аналізування інноваційної активності промислових підприємств України та, зокрема, Львівської області
Keywords: innovative activity; indicators of innovative activity; socio-economic development; competitiveness; інноваційна активність; показники інноваційної діяльності; соціально-економічний розвиток; конкурентоспроможність